Ber Tik-Tok: Sejauh Mana Bentuk Mengekspresikan Diri Dilakukan Dalam Perspektif Etika Kristiani - Simon Simon; Robi Panggarra; Reinhard Berhitu (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
The main focus of the discussion to be examined in this article is how the level of decency or reasonableness that Christians should do, when they express themselves in Tik Tok. This topic needs to be discussed, considering that the Tik Tok application is one of the social media that is favored by Indonesian people from various groups and religions. In working on this paper, the researcher uses a literature study and phenomenological approach to answer the research questions to be discussed. As for the question, what are the advantages and disadvantages of this media? What is the concrete form of self-expression that users do in Tik Tok? And what is the perspective of Christian ethics in Tik Tok? The result obtained is that the Tik Tok social media makes it easier for all content actors to go viral, both positive and negative, because the Tik Tok For You Page algorithm gives everyone equal opportunities. The dominant forms of self-expression in Tik Tok by users are dancing, dancing and lip syncing. As a result, elements of eroticism, sensuality by showing body curves and mocking are often carried out. The principle of Christian ethics strictly prohibits Christians from displaying a bad lifestyle, let alone being impolite. Because Christians are labeled as the epistle of Christ to be able to be an example in words and deeds as the light of the world.